Proceedings of the 1st International Conference on Science, Health, Economics, Education and Technology (ICoSHEET 2019) 2020
DOI: 10.2991/ahsr.k.200723.029
|View full text |Cite
|
Sign up to set email alerts
|

How is Picture Mnemonic Implemented in Teaching English Vocabulary to Students with Intellectual Disability?

Abstract: It is challenging for most teachers to teach English to students with intellectual disability. One of the reasons is because English is considered as a difficult subject especially for foreign language students, including students with intellectual disability. Furthermore, it is because students with intellectual disability have special characteristics which may become obstacles during teaching learning process. Intellectually disabled students tend to have a lack of motivation, low memory ability, to be passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This finding is consistent with other studies in the literature showing that technology-assisted implementations and implementing computerbased technology to help students learn vocabulary/phrases, spelling or writing skills in a foreign language are beneficial. (Flores et al, 2012;Kurniati et al, 2019;Rodrigues Carreon & Serrato Salavar, 2017;Seok et al, 2015;Van der Meer et al, 2012;Vedora & Stromer, 2007). In addition, the opinions of the participants of this study have a similarity to other studies in the literature on liking the activities which are done on the computer and not being bored which is beneficial for reflecting positively on their learning processes.…”
Section: Discussionsupporting
confidence: 62%
“…This finding is consistent with other studies in the literature showing that technology-assisted implementations and implementing computerbased technology to help students learn vocabulary/phrases, spelling or writing skills in a foreign language are beneficial. (Flores et al, 2012;Kurniati et al, 2019;Rodrigues Carreon & Serrato Salavar, 2017;Seok et al, 2015;Van der Meer et al, 2012;Vedora & Stromer, 2007). In addition, the opinions of the participants of this study have a similarity to other studies in the literature on liking the activities which are done on the computer and not being bored which is beneficial for reflecting positively on their learning processes.…”
Section: Discussionsupporting
confidence: 62%
“…In its application, this picture is used as a medium for teaching vocabulary to students, where the picture is a pictures about animals, things around the school, part of the body, and also combined with several things related to the type in part of speech. This makes students interested in the pictures that have been provided, in line with (Ristyani & Nurhayati, 2020), (Liando et al, 2021), (Mozes & Liando, 2020), (Agama & Singaraja, 2020), (Kurniati et al, 2020) and (Nurdini, 2018). From this data, it can be clearly seen that there is an increase from the students' pre-test to post-test.…”
Section: Resultsmentioning
confidence: 86%
“…Knowledge of vocabulary is basic and very important for students to master to communicate (Kurniati et al, 2020). The more vocabulary a student has, the more likely it is that the student is skilled in language or communication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that students' English learning achievement was better after being taught using the picture mnemonic strategy than before they were taught using the picture mnemonic strategy. It can be concluded that picture mnemonics effectively teach basic English for students with intellectual disabilities [12]. Furthermore, the authors also investigated the intellectually disabled behavior during English learning using mnemonics [13].…”
Section: Introductionmentioning
confidence: 99%